Hubungan Korelasional antara Motivasi Internal, Motivasi Eksternal, Kegiatan, dan Sense of Place di Hutan Kota - Riyad Maulana; Hanson E. Kusuma (RUAS, 2022)
The urban forest is a tourist destination in a natural urban environment. The relationship between visitor activities, the characteristics of the place, and the meaning of the place is very important in maintaining its nature. This research was conducted using mixed-method approach, with exploratory sequential design. The first stage explores the motivation for visiting and activities in the urban forest. The second stage reveals the correlation between internal, external motivational factors, activities, and a sense of place in the urban forest. The analysis used is factor analysis and multivariate correlation analysis, to look for relationships between dimensions that are formed based on measured variables. The results showed a correlation between internal motivation, external motivation, activities and a sense of place, interested in visiting the urban forest because of their physiological, psychological, natural environment, accessibility and relaxation needs. Meanwhile, they are very interested because of their social, cultural, recreational activities and seeing attractions.